Impact of Hydrostatic Pressure on an Intrinsically Disordered Protein: A High‐Pressure NMR Study of α‐Synuclein. Issue 14 (28th June 2013) - Roche, Julien; Ying, Jinfa; Maltsev, Alexander S.; Bax, Ad
Abstract The impact of pressure on the backbone 15N, 1H and 13C chemical shifts in N‐terminally acetylated α‐synuclein has been evaluated over a pressure range 1–2500 bar. Even while the chemical shifts fall very close to random coil values, as expected for an intrinsically disordered protein, substantial deviations in the pressure dependence of the chemical shifts are seen relative to those in short model peptides. In particular, the nonlinear pressure response of the 1HN chemical shifts, which commonly is associated with the presence of low‐lying "excited states", is much larger in α‐synuclein than in model peptides. The linear pressure response of 1HN chemical shift, commonly linked to H‐bond length change, correlates well with those in short model peptides, and is found to be anticorrelated with its temperature dependence. The pressure dependence of 13C chemical shifts shows remarkably large variations, even when accounting for residue type, and do not point to a clear shift in population between different regions of the Ramachandran map. However, a nearly universal decrease in 3JHN–Hα by 0.22±0.05 Hz suggests a slight increase in population of the polyproline II region at 2500 bar. The first six residues of N‐terminally acetylated synuclein show a transient of approximately 15 % population of α‐helix, which slightly diminishes at 2500 bar. The backbone dynamics of the protein is not visibly affected beyond the effect of slight increase in water viscosity at 2500 bar.